2023
DOI: 10.3390/antiox12030752
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Very Short Abstinence Period on Assisted Reproductive Technique Outcomes: A Systematic Review and Meta-Analysis

Abstract: Background: Previous studies supported the beneficial effects of a very short abstinence period on sperm quality. This systematic review and meta-analysis aimed to evaluate the effects of a very short abstinence period (within 4 h) on assisted reproductive technique (ART) outcomes. Methods: A literature search was performed using the Pubmed, Scopus, Web of Science, and Cochrane databases. A meta-analysis was performed according to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Evidence from this study indicated that nancial constraints were a major barrier to accessing IVF treatment. Other studies have emphasized that the cost of IVF treatment can be prohibitively expensive for many individuals, potentially preventing them from pursuing such treatment [20,21]. The high cost of IVF treatment is a well-documented factor and seems to be particularly impactful in the context of Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from this study indicated that nancial constraints were a major barrier to accessing IVF treatment. Other studies have emphasized that the cost of IVF treatment can be prohibitively expensive for many individuals, potentially preventing them from pursuing such treatment [20,21]. The high cost of IVF treatment is a well-documented factor and seems to be particularly impactful in the context of Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…The association between very short abstinence and ART outcomes has been investigated recently in a systematic review and meta-analysis by Barbagallo et al ( 53 ). The authors demonstrated significantly improved ART outcomes—implantation, clinical pregnancy, and live birth rates—following very short abstinence, compared to standard, 2 days or more, abstinence period in men with altered sperm parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a compelling systematic review suggests that the current evidence indicates that shorter abstinence periods lead to better clinical pregnancy and live birth rates ( 37 ). Furthermore, a recent systematic review and meta-analysis performed to compare very short abstinence periods on ART outcomes found that the implantation rate, clinical pregnancy rate, and live birth rate among these treatment-seeking couples improved significantly ( 38 ). We found that a short-interval second ejaculation could lead to a higher clinical pregnancy rate, implantation rate and live birth rate, but there were no significant differences due to the limited sample size.…”
Section: Discussionmentioning
confidence: 99%